Teacher Development for Bilingual Education in Colombia: Towards Teacher Empowerment - Anne-Marie Truscott de Mejía (Universidad de Navarra, 2016)
This article examines aspects of teacher education in Colombia with regard to demands posed by bilingual education and foreign language programmes. There is an initial overview of developments in the Americas, followed by a discussion of research conducted in Colombia in relation to the teaching of language and content area knowledge in a bilingual education context. The results of a recent study carried out on teacher empowerment are presented and there is a fi nal discussion of how far teacher education programmes enable practitioners to cope with tensions in their classroom practice, both in bilingual education and in foreign language settings.